Effect of emission on subnanosecond breakdown in a gas diode at low pressure; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Baksht E. Kh.; Belomyttsev S. Ya.; Burachenko A. G.; Grishkov A. A.; Shklyaev V. A. Valeriy Aleksandrovich (High-current electronics, 2017)
Title screen